Вплив агрегацiї на анiзотропiю перколяцiї на квадратнiй ґратцi в подовженiй геометрiї - Lebovka, N. I.; Bulavin, L. A.; Melnyk, I. A.; Repnin, K. F.; Kovalchuk, V. I. (Publishing house "Academperiodika", 2019)
The Monte Carlo simulation is applied to study the impact of the aggregation on the percolation anisotropy on a square lattice in the elongated Lx × Ly geometry. An interactive cluster-growth model, in which the probability of occupying a site on a lattice fz is dependent on the number of occupied neighboring sites z is used. The value of fz is 1/r at z = 0 and is equal to 1 in other cases. The degree of the aggregation parameter r ≥ 1 controls the morphology of aggregates. The transition from r = 1 to r → ∞ corresponds to the transition from the ordinary random percolation to the percolation of compact Eden clusters. The effects of the lattice aspect ratio a = Lx/Ly (Lx > Ly) on the finite-size scaling and the electrical conductivity are studied. The data evidence that the percolation threshold pc goes through the minimum, and the finite-size effects are enhanced with increase in r. The dependence of the electrical conductivity on the measuring direction (x or y) at different values of r and a is discussed.